(untitled) - Lovins, Amory B. (New York, 1977)
Soft Energy Paths is about ideas which have become much more familiar since its publication back in 1977 -- critiques of the "hard energy path" he describes as involving inefficient liquid-fuel automotive transport and centralized electricity generating facilities, often burning fossil fuels or using nuclear fission, technologies that waste huge amounts of energy and are enormously capital-intensive, along with advocacy of "soft energy technologies " such as solar, wind, biofuels, geothermal ...
Keywords: Power resources,Nguồn năng lượng,Energy policy,Chính sách năng lượng